EXAMINING THE DISTRIBUTION OF LANGUAGE SKILLS IN EFL TEXTBOOKS FOR JUNIOR HIGH SCHOOLS: PATTERNS, GAPS, AND PEDAGOGICAL SOLUTIONS - Opirman Waruwu; Rivaldo Branco Guterres (Research on English Language Education, 2026)
This study investigates the distribution of language skills in English for Nusantara, an EFL textbook published by the Indonesian Ministry of Education and Culture for Grade VIII students at the junior secondary level (SMP/MTs). Employing a mixed-method design, the study quantifies the frequency of listening, speaking, reading, viewing, and writing activities across the five chapters and fifteen units of the textbook, and proposes adaptive pedagogical strategies for teachers to address observed skill gaps. The quantitative findings reveal a notable imbalance: reading dominates at 36.4% of all skill-labeled sections, while speaking, writing, and viewing each account for approximately 11-14%, despite being explicitly mandated competencies under the Kurikulum Merdeka. Listening receives moderate coverage at 27.3% but is heavily concentrated in Unit 1 of each chapter. The qualitative phase presents close analyses of selected textbook activities and proposes five practical modifications integrating underrepresented skills without disrupting thematic coherence. While grounded in the Indonesian EFL context, the analytical framework and proposed solutions offer transferable insights for curriculum designers and classroom teachers working with comparable secondary-level EFL materials in other settings.